2017
DOI: 10.1002/arch.21438
|View full text |Cite
|
Sign up to set email alerts
|

RNA interference‐mediated knockdown and virus‐induced suppression of Troponin C gene adversely affect the behavior or fitness of the green rice leafhopper, Nephotettix cincticeps

Abstract: The green rice leafhopper, Nephotettix cincticeps, is a major rice pest in Southeast Asia and Southern China. Novel control strategies must be explored to control the rice pest. Behavior or fitness regulation of insect by modulating the Troponin C (TnC) may be a novel strategy in the comprehensive management of the insect pest. However, characterizations and functions of TnC, especially regarding effect of its RNA interference-mediated gene knockdown on the behavior or fitness of N. cincticeps remain unknown. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 52 publications
0
7
0
Order By: Relevance
“…We then investigated the transcript levels of these core components by RT-qPCR assay on a QuantStudio 6 Flex Real-Time PCR System (Life Technologies) using the SYBR Green PCR MasterMix kit (Promega) as described previously (Lan et al, 2015, 2018a). In total, we identified 14 core components of RNAi pathway in P. equestris genome, including DCL1, DCL2a, DCL3a, DCL4, AGO4B, AGO7, AGO10, AGO16, AGO-PNH1, AGO-MEL1, RdRP1, RdRP2, RdRP5, and RdRPSHL2 (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We then investigated the transcript levels of these core components by RT-qPCR assay on a QuantStudio 6 Flex Real-Time PCR System (Life Technologies) using the SYBR Green PCR MasterMix kit (Promega) as described previously (Lan et al, 2015, 2018a). In total, we identified 14 core components of RNAi pathway in P. equestris genome, including DCL1, DCL2a, DCL3a, DCL4, AGO4B, AGO7, AGO10, AGO16, AGO-PNH1, AGO-MEL1, RdRP1, RdRP2, RdRP5, and RdRPSHL2 (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, we used the sRNA target analysis server psRNATarget (Dai and Zhao, 2011) to predict putative target genes of P. equestris by CymMV- and ORSV-derived siRNAs. We then investigated the transcript levels of these core components and target genes by RT-qPCR assay on a Quant-Studio 6 Flex Real-Time PCR System (Life Technologies, Carlsbad, CA, USA) using the SYBR Green PCR Master-Mix kit (Promega, Madison, WI, USA) with primers (Table 1) as described previously (Lan et al, 2015, 2018a). …”
Section: Methodsmentioning
confidence: 99%
“…Troponin C (TnC), the Ca 2+ binding protein that initiates myocyte contraction, has been shown to play a role in enhancing the myofilament Ca 2+ sensitivity in fish (Gillis, Blumenschein, Sykes, & Tibbits, ). It is reported that knockdown of Nc‐TnC adversely affects the performance or fitness of Fabricius ( N. cincticeps ) and results in the decrease in survival, feeding capacity, weight, and fecundity (Lan et al, ). GLYA encodes serine hydroxymethyltransferase (SHMT) that catalyzes the conversion of serine and tetrahydrofolate, which play essential roles in cellular metabolism (Liu & Liu., ).…”
Section: Discussionmentioning
confidence: 99%
“…It is reported that knockdown of Nc-TnC adversely affects the performance or fitness of Fabricius (N. cincticeps) and results in the decrease in survival, feeding capacity, weight, and fecundity (Lan et al, 2018). GLYA encodes serine hydroxymethyltransferase (SHMT) that catalyzes the conversion of serine and tetrahydrofolate, which play essential roles in cellular metabolism (Liu & Liu., 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Total RNA and primer were denatured at 70 °C for 10 min, then 10 μL of Master Mix (Beyotime, Shanghai, China) was added before incubating at 42 °C for 1 h, then at 70 °C for 10 min. The about 500-bp fragment for TeMV was amplified using 2 μL cDNA as the template in a final volume of 50 μL with InvitrogenTM SuperScriptTM IV VILOTM kit (ThermoFisher, USA) [ 20 ] with an initial denaturation at 94 °C for 3 min; followed by 35 cycles at 94 °C for 1 min, 56 °C for 30 s, 72 °C for 45 s and 72 °C for 10 min. Healthy P. edulis samples were used as a control.…”
Section: Methodsmentioning
confidence: 99%